Making Inroads with the Outgroup: The Interactive Effects of Point of View and Group Membership in Period Poverty Narratives - Yin Yang; Chris Skurka (Journal of Public Interest Communications)
Over one billion people experience the threats that period poverty (lack of access to menstrual products) poses to their well-being. Public health advocates have used storytelling as a communication strategy to raise awareness and motivate behaviors that help address this issue. In an experiment with 1467 U.S. adults, we investigated the effects of period poverty narratives among individuals with different gender identities. Given a story can be told from different points of view (POV), we manipulated POV in period poverty narratives (first- or third-person) and examined moderating effects of gender identity. We found both narrative and non-narrative messages about period poverty can be effective, though a first-person narrative may hold the most promise for men when communicating about this issue.